(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With The Advances In Modern Technology, Need For Cloud Services Is Ever Increasing. In Such Case On Public Real-Time Cloud Environments The Workload On The Respective Server Can Vary Depending On The User Needs. Cloud Computing Is The Latest Technology That Provides On-Demand Availability Of Computer Resources Without Direct Intervention Of The User. This Technology Combined With Cloud Load Balancing Enables Enterprises To Manage Workload Demands. The Cloud Load Balancer, With Auto Scaling Features, Further Increases The Efficiency And Optimized Utilisation Of The Computing Resources. This Paper Discusses How Amazon Web Services As The Cloud Medium Along With Mobaxterm For Remote Control, And Implement ARR Configurations For The Load Balancer To Route The Requests. AWS Gives Us Knowledge About Various Concepts Such As Auto-Scaling Groups, Target Groups, Load Balancers, Etc.